RNA-Seq Analysis Identified XLOC_009190 as Potential Therapeutic Target for Lung Adenocarcinoma - Wang, Jing (Onco Targets Ther, 2019)
BACKGROUND: The abnormal regulation on the expression of lncRNAs had been linked to multiple kinds of cancers, including lung adenocarcinoma. METHODS: In this study, we carried out RNA-Seq on the three tumors and their paired normal samples from Chinese patients with lung adenocarcinoma. All the transcripts were de novo assembled, among which all the possible lncRNAs were predicted by tools including PLEK, CNCI, CPC, Blastp, hmmscan, and so forth. Their expression levels, altogether with the annotated mRNAs, were quantified. The weighted correlation network analysis and analysis of differential expression were carried out to explain the biological function of these novel lncRNAs. RESULTS: The weighted correlation network analysis showed that the lncRNAs, which were highly correlated with protein-coding genes, participated in various pathways, including PI3K kinase pathways. These lncRNAs were important regulators in biological processes. Next, the differentially expressed lncRNAs were identified, including four known lncRNAs and one novel lncRNA (XLOC_009190). The cis-regulation of this novel lncRNA might act on MGST1, which protected cells by conjugation and glutathione peroxidase functions. The trans-regulation of this lncRNA was investigated by its correlated mRNAs. The results showed that it possibly played a role in transmembrane receptors like G protein-coupled receptors and potassium channels. CONCLUSION: We proposed the potential biological function of XLOC_009190, but further experiments are needed to elucidate its roles and its potential to be the therapeutic target.